تأثير الرش بمحلول الإثيفون Ethephon في السلوك الجنسي لنبات الكوسا Cucurbita pepo L. وإنتاجيته - محرن, أحمد; بوراس, ميتيادي; زيدان, رياض; حميدان, مروان (Latakia University Journal -Biological Sciences Series, 2018)
جرت دراسة تأثير الرش المنفرد أو المتكرر بمحلول الإثيفون تركيز 250 ، 500 مغ/ل في السلوك الجنسي للهجين " مبروكة " من الكوسا وكمية المحصول خلال الموسم الربيعي لعام 2006. أظهرت نتائج الدراسة أن الرش المتكرر ثلاث مرات، وذلك بعد كل من الورقة الأولى، والثالثة والخامسة بمحلول الإثيفون تركيز 500 مغ/ل أدى إلى خفض النسبة الجنسية ( نسبة الأزهار المذكرة /المؤنثة) وتقليل عدد العقد غير الثمرية، مقابل زيادة عدد الأزهار المؤنثة، نسبة الأزهار المؤنثة/الكلية عدد الثمار على النبات، وإنتاجية النبات. كما أظهرت النتائج وجود علاقة ارتباطيه إيجابية قوية بين إنتاجية النبات وكل من عدد الأزهار المؤنثة ( r = + 0.98 ) ، ونسبة الأزهار المؤنثة / الكلية ( r = + 0.91 ) ، وعدد الثمار على النبات ( r = + 0.99 ). بينما كانت العلاقة سلبية قوية مع كل من النسبة الجنسية ( r = - 0.8 )، وعدد العقد غير الثمرية (r = - 0.95 )، وعدد الأزهار المذكرة على النبات ( r = - 0.88 ). The effect of singular or repeated foliar by two concentrations of ethephon solution (250 and 500 mg/l) on sex expression of squash hybrid "Mabrouka" and its productivity was studied. This study was conducted during the spring season 2006. Results showed that the foliar spray by ethephon solution (500 mg/l) 3 times after the 1st, 3ed, and 5ed leaf formation decreases the sexual ratio (male/female flowers) and the number of non fructifying nodes. In contrast, the number of female flowers, the female flowers/total flowers ratio, the number of fruits / plant, and the plant productivity increased. The results also showed a strong positive correlation between plant productivity and the number of female flowers ( r = 0.98), female/total flowers ratio ( r = 0.91) and the number of fruits/plant ( r = 0.99); whereas there was a strong negative correlation for the male/female flowers ratio ( r = -0.8), the number of non fructifying nodes (r = -0.95), and the number of male flowers /plant ( r = -0.88).